Digital Storytelling as an Innovative Element in English for Specific Purposes. (10th April 2015) - Gimeno-Sanz, Ana
Abstract: This paper discusses the benefits of using Digital Storytelling (DS) as an element of innovation and motivation with learners of English for Specific Purposes enrolled in Aerospace Engineering at the Universitat Politècnica de Valencia, Spain. The paper describes the context and the method, and concludes with a number of findings from a student survey that shed evidence to conclude that DS is a useful and engaging teaching approach with which students improve both non-linguistic skills and competences, as well as productive linguistics skills.